PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA SMP NEGERI 9 MEDAN - Ade Novita Sari Harahap; Imelda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the conceptual understanding of mathematics among eighth-grade students at SMP Negeri 9 Medan through the implementation of the Problem Based Learning (PBL) model combined with the Teaching at the Right Level (TaRL) approach. The research method used was Classroom Action Research (CAR), based on the model developed by Kurt Lewin and further modified by Kemmis and McTaggart. The research was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects were 32 students from class VIII-4. Data were collected through observation and conceptual understanding tests. The results showed that the combination of PBL and TaRL effectively improved students' conceptual understanding. The percentage of learning mastery increased from 25% in the pre-action stage to 59.38% in the first cycle, and reached 81.25% in the second cycle. These findings indicate that the integration of PBL and TaRL had a positive impact on students’ mathematics learning outcomes, particularly on the topic of triangle congruence.